Commentary. A picture of Mitf in melanoma immortality. - Goding, C (2011)
The Mitf gene has a key role in melanocytes and melanoma by regulating cell cycle progression, survival and differentiation. Two papers in this issue of Oncogene (Cheli et al., 2011; Strub et al., 2011) reveal that low-Mitf cells can initiate tumors with high efficiency, and that Mitf blocks senescence by regulating genes implicated in S-phase progression and mitosis.